Mesencephalic Astrocyte-Derived Neurotrophic Factor Regulates Morphology of Pigment-Dispersing Factor-Positive Clock Neurons and Circadian Neuronal Plasticity in Drosophila melanogaster - Krzeptowski, Wojciech; Walkowicz, Lucyna; Krzeptowska, Ewelina; Motta, Edyta; Witek, Kacper; Szramel, Joanna; Al Abaquita, Terence; Baster, Zbigniew; Rajfur, Zenon; Rosato, Ezio; Stratoulias, Vassilis; Heino, Tapio I.; et al. (Frontiers in Physiology, 2021)
Mesencephalic Astrocyte-derived Neurotrophic Factor (MANF) is one of a few neurotrophic factors described in Drosophila melanogaster (DmMANF) but its function is still poorly characterized. In the present study we found that DmMANF is expressed in different clusters of clock neurons. In particular, the PDF-positive large (l-LNv) and small (s-LNv) ventral lateral neurons, the CRYPTOCHROME-positive dorsal lateral neurons (LNd), the group 1 dorsal neurons posterior (DN1p) and different tim-positive cells in the fly’s visual system. Importantly, DmMANF expression in the ventral lateral neurons is not controlled by the clock nor it affects its molecular mechanism. However, silencing DmMANF expression in clock neurons affects the rhythm of locomotor activity in light:dark and constant darkness conditions. Such phenotypes correlate with abnormal morphology of the dorsal projections of the s-LNv and with reduced arborizations of the l-LNv in the medulla of the optic lobe. Additionally, we show that DmMANF is important for normal morphology of the L2 interneurons in the visual system and for the circadian rhythm in the topology of their dendritic tree. Our results indicate that DmMANF is important not only for the development of neurites but also for maintaining circadian plasticity of neurons.